Biserica și „Generația dopaminei”: Introducere în (psiho)terapia pastorală a dependențelor - Tia, Teofil; Foltiș, Grigorie (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The study is an introduction to the complex problems of today’s generation of young people, a generation suggestively called the „dopamine generation”; it creates the premises for a rigorous reflection on the forms through which the Orthodox Church can express its pastoral responsibility towards this generation, especially by articulating a coherent form of integrative psychotherapy (with a pastoral identity), which mitigates the harmful impact of new technologies on the more vulnerable categories. After operating some terminological and content nuances (one is vulnerability, another is chronic disease), it finds that digital addiction is a threat to public health in the Euro-Atlantic space, spreading tentacularly especially in the university universe; subsequently, two toxic effects of this addiction are briefly analyzed: insomnia (true psychiatric emergency) and the collapse of school per- formance. Finally, some guidelines are outlined for articulating professional forms of digital „detoxification”.